Do listeners recover “deleted” final /t/ in German? - Zimmerer, Frank; Reetz, Henning (Frontiers in Psychology, 2014)
Reduction and deletion processes occur regularly in conversational speech. A segment that is affected by such reduction and deletion processes in many Germanic languages (e.g., Dutch, English, German) is /t/. There are similarities concerning the factors that influence the likelihood of final /t/ to get deleted, such as segmental context. However, speakers of different languages differ with respect to the acoustic cues they leave in the speech signal when they delete final /t/. German speakers usually lengthen a preceding /s/ when they delete final /t/. This article investigates to what extent German listeners are able to reconstruct /t/ when they are presented with fragments of words where final /t/ has been deleted. It aims also at investigating whether the strategies that are used by German depend on the length of /s/, and therefore whether listeners are using language-specific cues. Results of a forced-choice segment detection task suggest that listeners are able to reconstruct deleted final /t/ in about 45% of the times. The length of /s/ plays some role in the reconstruction, however, it does not explain the behavior of German listeners completely.